Penguatan Pendidikan Karakter Pada Komunitas Adat Dayak Meratus - Ahmad Herman (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2023)
ABSTRACT Character education is one of the activities that aims to educate future generations by perfecting students self by training their self-ability towards a better life. This study aims to analyze: 1) Strengthening character values ​​education for the Dayak Meratus indigenous community at Balai Kiyu and Balai Atiran, Batang Alai Timur District, Hulu Sungai Tengah Regency. 2) The function and role of Balai Kiyu and Balam Atiran in preserving the character values ​​upheld by the Dayak Meratus indigenous community. 3) The function and role of the Regional Government in fostering Balai Kiyu and Balai Atiran in preserving the character values ​​that are upheld by the Dayak Meratus indigenous community; and 4) Strategic steps in preserving the character values ​​of the Dayak Meratus indigenous community. The research approach is a descriptive qualitative approach. Data collection through triangulation with Balian research subjects, traditional heads, village heads, heads of the Education Office. The results of the research are as follows: 1) Strengthening character values ​​education that is upheld in the form of traditional ceremonies and forest and land management principles, but there are still distortions; 2) The function and role of the adat hall is only as a symbol of identity, unifying for the Meratus Dayak customary community has not fully reached the implementation of strengthening character education; 3) The function and role of the government has not fully provided guidance in preserving the character values ​​of the Meratus Dayak indigenous community, still limited to tourism and arts promotion; 4) The strategic steps taken are to realize local wisdom based on the character values ​​of the Dayak Meratus customary community, encourage legal guarantees for character values ​​that are upheld in the form of Regional Regulations, and strive to maximize the function of the adat hall as a center for Balian integrated education. Keywords: Character Strengthening, Traditional Influence, Huma and Fields, Balian, and Balai. ABSTRAK Pendidikan karakter merupakan salah satu kegiatan yang bertujuan untuk mendidik generasi akan datang dengan cara menyempurnakan diri siswa dengan melatih kamampuan diri menuju ke arah hidup yang lebih baik. Penelitian ini bertujuan untuk menganalisis: 1) Penguatan pendidikan nilai-nilai karakter komunitas adat Dayak Meratus pada Balai Kiyu dan Balai Atiran Kecamatan Batang Alai Timur Kabupaten Hulu Sungai Tengah. 2) Fungsi dan peran Balai Kiyu dan Balam Atiran dalam melestarikan nilai-nilai karakter yang dijunjung tinggi komunitas adat Dayak Meratus. 3) Fungsi dan peran Pemerintah Daerah dalam membina Balai Kiyu dan Balai Atiran dalam melestarikan nilai-nilai karakter yang dijunjung tinggi komunitas adat Dayak Meratus; dan 4) Langkah strategis dalam melestarikan nilai-nilai karakter komunitas adat Dayak Meratus. Pendekatan penelitian adalah pendekatan kualitatif deskriptif. Pengumpulan data melalui triangulasi dengan subjek penelitian balian, kepala adat, kepala desa, kepala Dinas Pendidikan. Hasil penelitian sebagai berikut: 1) Penguatan pendidikan nilai-nilai karakter yang dijunjung tinggi dalam bentuk upacara adat dan prinsip pengelolaan hutan dan lahan, namun masih terdapat distorsi; 2) Fungsi dan peran balai adat hanya sebagai sebagai simbol identitas, pemersatu bagi komunitas adat Dayak Meratus belum sepenuhnya menjangkau pada implementasi penguatan pendidikan karakter; 3) Fungsi dan peran pemerintah belum sepenuhnya melakukan pembinaan dalam pelestarian nilai karakter komunitas adat Dayak Meratus, masih sebatas pada promosi wisata dan kesenian; 4) Langkah strategis yang dilakukan adalah merealisasikan kearifan lokal berbasis pada nilai-nilai karakter komunitas adat Dayak Meratus, mendorong adanya jaminan hukum nilai-nilai karakter yang dijunjung tinggi dalam bentuk Peraturan Daerah, dan mengupayakan pemaksimalan fungsi balai adat sebagai sentra pendidikan ke-balian-an. Kata Kunci: Penguatan Karakter, Aruh adat, Huma dan Ladang, Balian, dan Balai